2007
DOI: 10.1002/anie.200702363
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Reactions Involving Formal [2+2] Thermal Cycloadditions: Total Synthesis of Artochamins F, H, I, and J

Abstract: Dedicated to Masakatsu Shibasaki on the occasion of his 60th birthdayThe Artocarpus genus encompasses approximately 60 species of trees that are distributed throughout the tropical regions of Asia. Selected members of this family of plants have been used as traditional folk medicines in Sri Lanka, Taiwan, Thailand, and Indonesia. [1][2][3][4] A search for the bioactive ingredients of these plants led to the isolation of several bioactive prenylated flavanoids from the roots of Artocarpus chama, [5] and more re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Nicolaou and co-workers 30 have shown that the synthesis of the key artochamin intermediate could be generated via a cascade sequence involving a microwave-assisted [3,3] sigmatropic rearrangement of the appropriately functionalized stilbene, followed by a [2+2] cycloaddition of the generated intermediate at 180 1C in the presence of a catalytic amount of Ph 3 PO in o-xylene for 20 min (Scheme 24). The precise role of Ph 3 PO is unclear.…”
Section: Microwave-assisted [2+2] Cycloaddition Reactionsmentioning
confidence: 99%
“…Nicolaou and co-workers 30 have shown that the synthesis of the key artochamin intermediate could be generated via a cascade sequence involving a microwave-assisted [3,3] sigmatropic rearrangement of the appropriately functionalized stilbene, followed by a [2+2] cycloaddition of the generated intermediate at 180 1C in the presence of a catalytic amount of Ph 3 PO in o-xylene for 20 min (Scheme 24). The precise role of Ph 3 PO is unclear.…”
Section: Microwave-assisted [2+2] Cycloaddition Reactionsmentioning
confidence: 99%
“…Nicolaou et al (2007) have carried out the synthesis of the key artochamin intermediate via a cascade sequence involving a microwave-assisted [3,3] sigmatropic rearrangement of the appropriately functionalized stilbene, which was followed by a [2+2] cycloaddition of the generated intermediate at 180°C in the presence of a catalytic amount of Ph 3 PO in o-xylene in 20 min. The yield of 55% was obtained.…”
Section: [2+2] Cycloadditionmentioning
confidence: 99%
“…[26] We therefore adopted a reverse deprotection sequence, with the debenzylation being affected first followed by LiAlH 4 -mediated depivoylation. [27] Pleasingly, this new protocol allowed for the successful synthesis of (+)-gallocatechin (3) in 42 % yield via a debenzylation-depivoylation sequence (Scheme 6).…”
mentioning
confidence: 99%